Effect of cinnamon tea on postprandial glucose concentration - Bernardo, Maria Alexandra (2015)
"Glycaemic control, in particular at postprandial period, has a key role in prevention of different diseases, including diabetes and cardiovascular events. Previous studies suggest that postprandial high blood glucose levels (BGL) can lead to an oxidative stress status, which is associated with metabolic alterations. Cinnamon powder has demonstrated a beneficial effect on postprandial glucose homeostasis in animals and human models. The purpose of this study is to investigate the effect of cinnamon tea (C. burmannii) on postprandial capillary blood glucose level on nondiabetic adults. Participants were given oral glucose tolerance test either with or without cinnamon tea in a randomized clinical trial. The data revealed that cinnamon tea administration slightly decreased postprandial BGL. Cinnamon tea ingestion also results in a significantly lower postprandial maximum glucose concentration and variation ofmaximum glucose concentration (p < 0.05). Chemical analysis showed that cinnamon tea has a high antioxidant capacity, whichmay be due to its polyphenol content. The present study provides evidence that cinnamon tea, obtained from C. burmannii, could be beneficial for controlling glucose metabolism in nondiabetic adults during postprandial period."